TINJAUAN YURIDIS PENCEGAHAN PENYELUNDUPAN BALLPRESS DI WILAYAH HUKUM KEPOLISIAN RESORT ASAHAN DALAM PERSPEKTIF KUHP (Studi Putusan Nomor 85/Pid. Sus/2018/PN. Tbk) - Dian Pranata Simangunsong; Nelvitia Purba; Ibnu Affan (Jurnal Ilmiah METADATA, 2021)
The crime of smuggling is very rampant in Indonesia, it's just that in imposing criminal sanctions, its implementation only focuses on imprisonment, because the formulation of the Customs Law is not explicitly regulated on the concept of returning state losses, so that every time a criminal act of smuggling occurs, the state is always at a loss. The problems in this discussion are how to regulate the law regarding the illegal smuggling of used clothes in the Republic of Indonesia, how the obstacles and efforts made by the Asahan Resort police in preventing ballpress smuggling, how to enforce the law against the perpetrators of the ballpress smuggling crime in the decision Number 85/Pid. Sus/2018/PN.Tbk. This study uses a descriptive method through a normative approach (legal research), namely an approach to problems, carried out by examining various legal aspects in terms of applicable regulations. The results of the study show that the legal regulation of smuggling in Indonesia is regulated in Law no. 17 of 2006 concerning Customs, Decree of the Minister of Industry and Trade No. 229/MPP/Kep/7/1997 that imported goods must be in a new condition and Decree of the Minister of Industry and Trade No. 642/MPP/Kep/9/2002 concerning Changes Appendix I No.230/MPP/Kep/7/1997 states that new and used rags are prohibited for import by importers to enter Indonesia and Regulation of the Minister of Trade of the Republic of Indonesia Number 51/M-DAG/PER/2015 concerning the Prohibition of the Import of Used Clothing . The obstacles that the Asahan Resort police do in preventing ballpress smuggling are perpetrators who provide fictitious information during the examination process. Efforts to prevent criminal acts of smuggling are carried out with 2 kinds of efforts, namely preventive and repressive efforts. Law enforcement against perpetrators of criminal acts of ballpress smuggling in Decision Number 85/Pid.Sus/2018/PN. Tbk is the perpetrator sentenced to imprisonment for 2 (two) years and a fine of Rp. 50,000,000, - (fifty million rupiah) provided that if the fine is not paid, it is replaced with imprisonment for 3 (three) months.